Educación y sociedad en Iberoamérica : ensayos en homenaje a Juan Carlos Rodríguez Ibarra / Miguel Rojas Mix (editor) - Rodríguez Ibarra, Juan Carlos (1948-) Rojas Mix, Miguel
Incluye referencias bibliográficas